From Remedial to Preventive Justice: A Contemporary Reframing of Civil Liability in Islamic and Comparative Law - Salah Eldin Ragab Semida; Zeyad Tareq Al-Rawe; Sarmad Dalaf Hanoosh; Tarek El-Sayed Mahmoud Abu Aqil; Mahmood Shaker Alaloosh (MILRev: Metro Islamic Law Review, 2026)
This study examines the evolution of civil liability from its traditional compensatory function toward a preventive model capable of addressing contemporary technological, environmental, and industrial risks. The research aims to analyze the legal foundations of the preventive function of civil liability, identify gaps in modern legislation, particularly in Arab jurisdictions, and explore how principles derived from Islamic jurisprudence can enhance contemporary legal frameworks. The study adopts a descriptive and comparative analytical methodology, examining statutory provisions, judicial rulings, and doctrinal writings in selected legal systems, including French, Chinese, and Indonesian law, alongside Islamic juristic maxims grounded in uṣūl al-fiqh, particularly the principles of lā ḍarar wa lā ḍirār and sadd al-dharāʾiʿ. The findings reveal that modern legal systems increasingly recognize preventive liability through mechanisms such as judicial injunctions, the duty of care, elimination-of-danger actions, and public interest litigation. However, these mechanisms vary in scope and philosophical foundation, and many Arab civil codes lack explicit and coherent preventive provisions. In contrast, Islamic jurisprudence offers a deeply rooted preventive framework that prioritizes averting harm over compensating for it, grounding liability in ethical responsibility and risk avoidance rather than solely in actual damage. The study concludes that integrating preventive principles into civil liability is both a legal and ethical necessity in the era of complex risks. It proposes a forward-looking legislative framework combining comparative legal techniques with Islamic preventive maxims to strengthen risk management and judicial intervention. Academically, the research contributes a novel comparative model that bridges Islamic jurisprudence and contemporary civil law theory, reconceptualizing liability as a proactive instrument of preventive justice rather than a merely remedial mechanism.